Quality Assurance and Learners’ Learning Effectiveness: University of Ibadan Distance Learning Centre Experience - Quadri, Ganiyu Oluwaseyi; Muibi , Taofeek Gbolahan; Ukpere, Wilfred Isioma (Journal of Economic Development, Environment and People, 2025)
Quality assurance and concern for distance learning programmes (DLPs) are necessary due to the significance of quality control for student satisfaction and enrolment. In light of this, this study investigated how learners' learning effectiveness (LE) within the institution was impacted by quality assurance mechanisms (QAM) such as course design (CD), effective teaching and learning (ETL), assessment and evaluation procedures (AEP), learner support services (LSS), and environmental infrastructure (EI). The study design that was used was a descriptive survey. 200 students were selected at random from the faculties of arts, education, and social sciences (FAESS), totalling up the population of 100–500 level students. Part of the research included a 30-item survey on the Perceived QAM Implementation on LE in Distance Education Scale (r=.81). The data were analysed with descriptive statistics and the Pearson Product-Moment Correlation (PPMC) at the 0.05 threshold of statistical significance. The findings demonstrated that CD (r=0.76), teaching and learning approaches (TLA) (r=0.62), AEP (r=0.57), LSS (r=0.45), and EI (r=0.49) had positive and significant correlations with students' LE. Also, CD, ETL, AEP, LSS, and EI contributed to students' LE in the institution. In light of the results, the research suggested that the leadership of the University of Ibadan's (UI) Distance Learning Centre (DLC) should set up efficient guidelines and a management framework to handle different facets of quality assurance (QA) and ensure the effective implementation of these policies in order to support and improve students' LE. This proactive approach would ensure compliance with the rigorous demands of 21st-ccentury education. This unique research on QAM and students' LE was carried out at DLC, UI.